Short-term propofol anaesthesia down-regulates clock genes expression in the master clock. (2nd December 2018) - Ben-Hamouda, Nawfel; Poirel, Vincent-Joseph; Dispersyn, Garance; Pévet, Paul; Challet, Etienne; Pain, Laure
ABSTRACT: Background : Propofol anesthesia triggers phase-advances of circadian rhythms controlled by the suprachiasmatic nuclei (SCN), the master clock. Besides, inhalational anesthesia has been associated with a subsequent reduction of Per2 mRNA levels in the whole brain of rodents. The acute effects of propofol anesthesia per se on the SCN molecular clockwork remain unclear. Here we aim to study the expression of Per1 and Per2 clock genes in the SCN of rats exposed to constant darkness after a single dose of propofol. Methods : Thirty 2-months old rats were randomly divided into 2 groups receiving a single dose of either 120 mg/kg propofol 1% (n=15), or intralipid® 10% (n=15) in late day (projected circadian time (CT) 10, i.e., 10h after the expected time of lights on). Thereafter, rat brains were sampled in darkness 1h, 2h or 3h after the treatment (projected CT11, CT12 or CT13). Expression of Per1 and Per2 mRNA was analyzed by in situ hybridization in SCN coronal sections. Results : Per1 expression was affected by time and treatment. Per1 expression in the SCN after propofol treatment decreased at CT11 and CT12 when compared to the vehicle group. For Per2 expression, we observed only a treatment effect. Observed in dark conditions without hypothermia or/and concomitant surgery, such down-regulation of clock genes Per is only correlated to propofol treatment. This may explain "jet-lag-like" symptoms described by patients after anesthesia. Conclusion : We show here for the first time that short-term propofol anesthesia leads to a transient down-regulation of Per1 and Per2 expression in the SCN.